Establishment and evaluation of an overlap extension polymerase chain reaction technique for rapid and efficient detection of drug-resistance in Mycobacterium tuberculosis - Jungang Li; Jing Ouyang; Jing Yuan; Tongxin Li; Ming Luo; Jing Wang; Yaokai Chen (BMC, 2022)
Abstract Background Rapid and accurate detection of drug resistance in Mycobacterium tuberculosis is critical for effective control of tuberculosis (TB). Herein, we established a novel, low cost strategy having high accuracy and speed for the detection of M. tuberculosis drug resistance, using gene splicing by overlap extension PCR (SOE PCR). Methods The SOE PCR assay and Sanger sequencing are designed and constructed to detect mutations of rpoB, embB, katG, and inhA promoter, which have been considered as the major contributors to rifampicin (RFP), isoniazid (INH), and ethambutol (EMB) resistance in M. tuberculosis. One hundred and eight M. tuberculosis isolates came from mycobacterial cultures of TB cases at Chongqing Public Health Medical Center in China from December 2018 to April 2019, of which 56 isolates were tested with the GeneXpert MTB/RIF assay. Performance evaluation of the SOE PCR technique was compared with traditional mycobacterial culture and drug susceptibility testing (DST) or GeneXpert MTB/RIF among these isolates. Kappa identity test was used to analyze the consistency of the different diagnostic methods. Results We found that the mutations of S531L, S315T and M306V were most prevalent for RFP, INH and EMB resistance, respectively, in the 108 M. tuberculosis isolates. Compared with phenotypic DST, the sensitivity and specificity of the SOE PCR assay for resistance detection were 100.00% and 88.00% for RFP, 94.64% and 94.23% for INH, and 68.97% and 79.75% for EMB, respectively. Compared with the GeneXpert MTB/RIF, the SOE PCR method was completely consistent with results of the GeneXpert MTB/RIF, with a concordance of 100% for resistance to RFP. Conclusions In present study, a novel SOE PCR diagnostic method was successfully developed for the accurate detection of M. tuberculosis drug resistance. Our results using this method have a high consistency with that of traditional phenotypic DST or GeneXpert MTB/RIF, and SOE PCR testing in clinical isolates can also be conducted rapidly and simultaneously for detection of drug resistance to RFP, EMB, and INH. Graphical Abstract